Multilingual Named Entity Recognition using Parallel Data and Metadata from Wikipedia - Kim, Sungchul; Toutanova, Kristina; Yu, Hwanjo (ACL, 2012)
In this paper we propose a method to automatically label multi-lingual data with named entity tags. We build on prior work utilizing Wikipedia metadata and show how to effectively combine the weak annotations stemming from Wikipedia metadata with information obtained through English-foreign language parallel Wikipedia sentences. The combination is achieved using a novel semi-CRF model for foreign sentence tagging in the context of a parallel English sentence. The model outperforms both standard annotation projection methods and methods based solely on Wikipedia metadata.